Walenty from Widawa (1537–1601), professor and rector of the Krakow Academy – an outline of biography and activity. Scholar’s book collection - Wichowa, Maria (Interdyscyplinarium nauk o mediach i kulturze, 2020)
Walenty from Widawa, the son of the burgher Wawrzyniec, began studies at the Krakow Academy in 1562, he graduated in 1569 receiving a master’s degree. In 1579 he began his theological studies and graduated in 1582 to obtain a baccalaureate, and after five years a doctorate in theology. He taught theology at the Faculty of Theology. In 1574 he became dean of the Faculty of Philosophy at the Krakow Academy, twice he was elected a rector: in the years 1595–1596 and 1600–1601. In his will, he wrote his collection, consisting of about 350 copies, to the parish of the Exaltation of the Holy Cross in Widawa. The text of this testament has survived in the archives of the Jagiellonian University, and in the files of the temple in Widawa, a catalog of books given by the rector Walenty to Widawa. Widavita’s library contained literary texts of Greek and Roman authors, dictionaries, grammar textbooks, old editions of the Bible, postillions, biblical commentaries, apostolic letters, sermons, chronicles, a catalog of church writers and numerous theological treatises, numerous texts by Polish authors. Widavita’s library is proof of the intellectual contacts of the professor with research and printing centers in Europe.